Association between fibromyalgia and cataract: A database retrospective cohort study. Issue 29 (23rd July 2021) - Hu, Wei-Syun; Lin, Cheng-Li; Chen, Tung-Sheng
Abstract : Abstract: This study was set to investigate whether fibromyalgia increased cataract risk. Fibromyalgia patients were the case group and controls were people who never had a history of fibromyalgia. We estimated the hazard ratio of cataract by Cox proportional-hazards model. The adjusted hazard ratios were obtained by controlling variables of age, sex, and comorbidities. Stratification analysis was also performed to ensure the association of fibromyalgia and cataract. We included 6949 participants in each groups. The incidence rate of cataract in patients with fibromyalgia (108.9 per 1000 person-years) was higher than that of control group (58.9 per 1000 person-years). The risk of cataract in fibromyalgia patients was 2.48 (95% confidence interval = 2.34–2.63) times higher than subjects without fibromyalgia. Fibromyalgia is associated with higher risk of cataract.